Potensi Penggunaan Eco Enzyme pada Degradasi Deterjen dalam Air Limbah Domestik - Efli Pratamadina; Temmy Wikaningrum (Fakultas Teknik, 2022)
Environmental pollution is one of the factors causing environmental damage. The environment can accept a certain level of pollutant load and can neutralize it within a certain period. But along with the development of human activities, the amount and level of pollutants are increasing inversely with the capacity of the environment and the ability of the environment to neutralize pollutants. One of the factors causing environmental pollution is domestic wastewater. This research uses orange waste to be processed into the eco enzyme. Making eco enzyme lasts for 3 months. Eco enzyme is made using orange waste, brown sugar, water in a ratio of 3:1:10, and fermentation time is 3 months. This study aims to determine whether the eco-enzyme of orange waste can be used to reduce the concentration of detergent in domestic wastewater. The method used in this research is an experimental method with a laboratory scale. From the experiments carried out, primary data will be obtained. Based on the eco-enzyme characterization of orange waste used, it is known that the concentration of detergent is 0.2534 mg/L. The concentration of detergent in domestic waste is 2.1464 mg/L. The concentration of detergent in domestic waste after added eco-enzyme of orange waste 5% becomes 0.68 mg/L and 10% becomes 0.30 mg/L with a detention time of 7 days.